The Polish growth miracle: outcome of persistent reform efforts - Hartmut Lehmann (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Since the beginning of transition in 1990 from a centrally planned to a market oriented economy, the performance of Poland's economy has been outstanding if we take GDP growth as our measure. In our opinion it is not specific reforms that can explain this performance but the radical ("big bang") reforms at the beginning of transition in conjunction with persistent efforts during the two decades by all governments, no matter what their political orientation, to keep on a reform path. Reforming a centrally planned economy that has very serious macroeconomic disequilibria implies reforms that can be done immediately but also structural or systemic reforms that require years to implement. Both types of reforms will be discussed. In a democratic context reforms can only be undertaken in a sustained way if a majority of voters favours such reform efforts. Even when reform-friendly governments were voted out of office in the Polish case, the new governments in Poland never reversed reforms undertaken by the previous government. This continuous reform stance over two decades is the main cause of the Polish growth miracle. The reasons for the ability of Polish policy makers to pursue economic and administrative reforms in spite of short-run costs to large sections of society will be discussed extensively
Keywords: D78; J40; P20; P26; 330